Radiology Critical Analysis of Patient Safety and Ethical Challenges in Radiological Practices - ALRESHIDI, MUSAAD SHURAYWID; ALQABBA, ABDULLAH HOMOUD ABDULLAH; ALRASHIDI, SAUD SAAD SAUD; ALHINDY, HADEEL KALED; ALMDINI, ASMA YAUSAF MOHAMMED; AL-SHAMMARI, NOURAH SAAD SUWAILEM; AL SHAMMARI, SAMI HAMOUD AWAD; ALSHAMMARI, FARIS MOHAMMED L; ALSHAMMARI, FRAIH FEHAID; AL SHAMMARI, SULTAN HAMOUD AWAD (Journal of Ecohumanism, 2024)
Radiology is one of the important specialties of medicine that plays a useful role in diagnosing and approaching different diseases. Nonetheless, as many patients depend on radiological imaging technologies, the factors that revolve around the safety of patients, as well as the ethical issues, come into play. This manuscript seeks to provide a critical review of patient safety concerns in radiology, emphasizing radiation protection, technology, and ethical issues accompanying innovations in imaging services. The strategies to deal with these issues are also examined, together with the role of the radiologist in addressing these problems and the significance of patient consent and patient-oriented care practices within the scope of radiology. In responding to these issues, the present paper shall endeavor to engender further informed debate on the appropriate propagation of radiology today.